Improving the intergranular corrosion resistance of austenitic stainless steel by high density twinned structure. (15th March 2017) - Chen, A.Y.; Hu, W.F.; Wang, D.; Zhu, Y.K.; Wang, P.; Yang, J.H.; Wang, X.Y.; Gu, J.F.; Lu, J.
Abstract: We investigated the effect of high density twins on the intergranular corrosion (IGC) of austenitic stainless steel after sensitization. The twinned samples, especially the one with a twin density over 86% area fraction, exhibited a remarkable IGC resistance, characterized by a higher corrosion potential, a broader passivation zone, and a lower corrosion rate. The chromium depletion was inhibited by the twin boundaries emitted at grain boundaries, while the passivation was enhanced by the chromium enrichment at nanotwins inside the coarse grains. Graphical abstract: Figure Surface morphologies of the sensitized 304 SS, TW-100 and TW-250 samples after etching 4 and 35 h in 65% HNO3 solution at boiling temperature.